Charge-carrier trapping dynamics in bismuth-doped thin films of MAPbBr3 perovskite - Ulatowski, AM; Wright, AD; Wenger, B; Buizza, LRV; Motti, SG; Eggimann, HJ; Savill, KJ; Borchert, J; Snaith, HJ; Johnston, MB; Herz, LM (American Chemical Society, 2020)
Successful chemical doping of metal halide perovskites with small amounts of heterovalent metals has attracted recent research attention because of its potential to improve long-term material stability and tune absorption spectra. However, some additives have been observed to impact negatively on optoelectronic properties, highlighting the importance of understanding charge-carrier behavior in doped metal halide perovskites. Here, we present an investigation of charge-carrier trapping and conduction in films of MAPbBr3 perovskite chemically doped with bismuth. We find that the addition of bismuth has no effect on either the band gap or exciton binding energy of the MAPbBr3 host. However, we observe a substantial enhancement of electron-trapping defects upon bismuth doping, which results in an ultrafast charge-carrier decay component, enhanced infrared emission, and a notable decrease of charge-carrier mobility. We propose that such defects arise from the current approach to Bi-doping through addition of BiBr3, which may enhance the presence of bromide interstitials.